IMPACT OF MESSAGE DESIGN ON DISPLAY ADS INVOLVEMENT AND EFFECTIVENESS: AN EVIDENCE FROM INDIA - Dr. Bijay Prasad Kushwaha (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The digital advertising budget is increasing day-by-day. Even new marketers are also entering into digital marketing. The biggest challenge in this form of advertisement is engaging customers with ads and making it an effective marketing campaign. Display ads is an online marketing tool which allows marketers to promote their offering in the form of text, image, and banner. The objective of this study is to find out the factors that help to involve the target audience with ads and makes an effective online campaign. This study has taken personalisation, content, and design of display ads as factors that increase the involvement of the target audience and click-through-rate. The click-through-rate determines the effectiveness of display ads. The convenience sampling technique was applied to identify 358 samples of Greater Mohali. The finding of the study suggests that the design of display ads is the most important factor which grabs the attention of users on the display network websites. The smart PLS-SEM 3.0 was used to analyses and establish the framework of effective display ads.